Reflections upon the Privacy in the Converged Commercial Radio: A Case Study of Royal Prank - Stachyra, Grażyna (2020)
This article focuses on the problematic consequences of shifting boundaries of converged radio practices for individual privacies. Holding that privacy is constructed through the interrelated information practices of both individuals and their mediated surroundings, it addresses radio as a previously intimate and privacy friendly medium. The case of the Royal Prank call by the Australian 2DayFM radio station demonstrates how contemporary converged radio practices affect the privacies of unintended participants in their shows. In December 2012, Jacintha Saldanha, nurse of London’s Royal King Edward VII Hospital committed suicide after two Australian radio presenters had made a prank phone call pretending to be Queen Elizabeth and Prince Charles concerned about the state of Duchess Kate’s health, who was expecting her first child. The case identifies three conditions, each with implications on privacy. First, digitization renders radio content archivable and repeatable. There is a second life of radio programs keeping available information about any people involved. Secondly, the division of radio related labour leads to a lack of journalistic responsibility for respecting privacy standards. Broadcasters feel no need to be sensitive regarding the consequences of disseminated material, as commercial and legal staff decide on that. Finally, legal frameworks continue to apply legacy radio privacy measures and do not correspond to these new working conditions, as the reactions of the Australian supervisory authority show. In consequence, the case of the Royal Prank call demonstrates the impossibility to fight individual privacy when one is unintentionally involved in radio shows.